Polynomial complexity despite the fermionic sign. (30th May 2017) - Rossi, R.; Prokof'ev, N.; Svistunov, B.; Van Houcke, K.; Werner, F.
Abstract: It is commonly believed that in unbiased quantum Monte Carlo approaches to fermionic many-body problems, the infamous sign problem generically implies prohibitively large computational times for obtaining thermodynamic-limit quantities. We point out that for convergent Feynman diagrammatic series evaluated with a recently introduced Monte Carlo algorithm (see Rossi R., arXiv:1612.05184), the computational time increases only polynomially with the inverse error on thermodynamic-limit quantities.